Vitamin D in Type 2 Diabetes: Genetic Susceptibility and the Response to Supplementation - Klahold, Edith; Penna-Martinez, Marissa; Bruns, Franziska; Seidl, Christian; Wicker, Sabine; Badenhoop, Klaus (Hormone and Metabolic Research, 2020)
Variants of vitamin D metabolism-genes may predispose to type 2 diabetes (T2D). This study investigated the impact of these variants on disease susceptibility, Vitamin D, parathyroid hormone, C-peptide and HbA1c levels before and after cholecalciferol supplementation in patients with T2D.Twelve polymorphisms within CYP2R1, CYP27B1, DBP, VDR and CYP24A1 were genotyped in 553 T2D patients and 916 controls. In addition 65 patients receiving either cholecalciferol or placebo were analyzed during 6 months intervention and 6 months follow-up.T2D risk alleles are VDR rs7975232 “G” (pc=0.031), rs1544410 “G” (pc=0.027) and CYP2R1 rs10741657 “A” (pc=0.016). Patients with genotypes CYP27B1 rs10877012 “CC” (pc=4x10-5), DBP rs7041 “GG” (pc=0.003), rs4588 “CC” (pc = 3x10-4), CYP24A1 rs2585426 “CG” (pc=0.006) and rs2248137 “CG” (pc=0.001) showed lower 25(OH)D3 and DBP rs4588 “CC” lower 1,25(OH)2D3 levels (pc=0.005). Whereas DBP rs4588 “CC” (pc=0.009), CYP27B1 rs10877012 “AC” (pc=0.059), VDR rs7975323 “AG” (pc=0.033) and rs1544410 “GG” (pc=0.013) are associated with higher 25(OH)D3 levels at 6 months’ follow-up. Significant PTH suppression was detected for CYP2R1 “AG“ (pc=0.002), DBP rs4588 “CC” (pc<0.001), VDR rs110735810 “CT” (pc<0.001) and CYP24A1 rs2248137 “GG” (pc=0.021).Genetic variants of the vitamin D system predispose to type 2 diabetes and regulate – partially - vitamin D metabolism, concentrations and the vitamin D status. Vitamin D insufficiency is a T2D risk factor. The response to cholecalciferol supplementation can be measured as 25(OH)D3 increment and PTH suppression. This process is regulated by genes of the vitamin D system conferring modest T2D risk.
Keywords: CYP2R1; CYP27B1; DBP; VDR; CYP24A1; GC